Raf induces NF-κB by membrane shuttle kinase MEKK1, a signaling pathway critical for transformation - Baumann, Bernd (The National Academy of Sciences, 2000)
NF-κB is regulated by inhibitor proteins (IκBs), which retain NF-κB in the cytoplasm. Signal-induced phosphorylation by the IκB-kinase complex containing the IκB-kinases 1 and 2 (IKK-1/2 or IKK-α/β) and subsequent degradation of the IκB proteins are prerequisites for NF-κB activation. Many signals induce NF-κB, one of them being oncogenic Raf kinase. We investigated whether NF-κB induction is critical for Raf-mediated transformation. Here, we demonstrate that inhibition of NF-κB interferes with transformation by the Raf-oncogene, and we characterized the mechanism of NF-κB induction by activated Raf kinase and the tumor promoter phorbol 12-myristate 13-acetate (PMA). NF-κB activation by PMA and Raf critically depends on the IκB-kinase complex, most notably on IKK-2. A major signaling pathway induced by Raf is the mitogenic cytoplasmic kinase cascade. However, different inhibitors of this cascade do not affect PMA- and Raf-mediated NF-κB activation. Raf does not phosphorylate the IκB-kinase proteins directly. Raf rather synergizes with another membrane shuttle kinase MEKK1, and Raf-mediated activation of NF-κB is blocked by a dominant negative form of MEKK1. These results suggest that Raf induction of NF-κB is relayed by MEKK1, but not by the classical mitogenic cytoplasmic kinase cascade.